Studi Historis-Fungsional atas Kisah-Kisah dalam Al-Qur’an - Nurzaman, Nurzaman; Kamal, Mustopa (Research and Development Institution, Darussalam Institute for Islamic Studies, 2018)
This research aims to elaborate the stories in the Alquran, both historically and based on their functions and uses. By using a functional study of the stories in the Qur’an, this article attempts to open up various aspects of qashash al-Qur’ân, especially with regard to its functions, implications and benefits to Muslims. The implications of these stories on the ethical-spiritual dimensions of Muslims are reviewed by many authors. Although some of the stories in the Qur’an remain unproven today, their influence remains strong on the ethics and spiritual life of Muslims. Among Muslims, and other religious communities, the stories in the scriptures always become a reference in everyday life. The stories are transmitted through educational, social, family and cultural institutions. The stories of the Scriptures are always seen as sacred, sacred, and contain transcendent power.